2017
DOI: 10.1158/1535-7163.mct-16-0678
|View full text |Cite
|
Sign up to set email alerts
|

Selective Killing of SMARCA2- and SMARCA4-deficient Small Cell Carcinoma of the Ovary, Hypercalcemic Type Cells by Inhibition of EZH2: In Vitro and In Vivo Preclinical Models

Abstract: The SWI/SNF complex is a major regulator of gene expression and is increasingly thought to play an important role in human cancer, as evidenced by the high frequency of subunit mutations across virtually all cancer types. We previously reported that in preclinical models, malignant rhabdoid tumors, which are deficient in the SWI/SNF core component INI1 (SMARCB1), are selectively killed by inhibitors of the H3K27 histone methyltransferase EZH2. Given the demonstrated antagonistic activities of the SWI/SNF compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
103
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(111 citation statements)
references
References 45 publications
7
103
0
1
Order By: Relevance
“…Our present study demonstrated that the methyltransferase EZH2 can serve as a potential therapeutic target for this deadly disease. While our manuscript was in review, an independent manuscript confirming some of our findings was published . Although both papers described the preclinical potency of EZH2 inhibition in SCCOHT, we substantiated this effect with two distinct EZH2 inhibitors for both in vitro and in vivo studies.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our present study demonstrated that the methyltransferase EZH2 can serve as a potential therapeutic target for this deadly disease. While our manuscript was in review, an independent manuscript confirming some of our findings was published . Although both papers described the preclinical potency of EZH2 inhibition in SCCOHT, we substantiated this effect with two distinct EZH2 inhibitors for both in vitro and in vivo studies.…”
Section: Discussionsupporting
confidence: 64%
“…Western blotting analysis demonstrated that two SCCOHT cell lines, BIN67 and SCCOHT‐1, expressed EZH2 protein at a level comparable to or higher than that of several other ovarian cancer cell lines and the MRT cell line G401 (Figure B). COV434, a cell line originally designated as a juvenile granulosa cell tumour cell line but recently redefined as a SCCOHT cell line with SMARCA4/SMARCA2 dual deficiency , also abundantly expressed EZH2 protein (Figure B). The expression levels of H3K27me3 were remarkably high in all three SCCOHT lines and G401, while only three out of seven other ovarian cancer lines expressed H3K27me3 at a similar abundance.…”
Section: Resultsmentioning
confidence: 99%
“…33 Patients with SMARCA4-deficient UUS may benefit from enrolment in ongoing clinical trials using tazemetostat, a selective small molecule EZH2 inhibitor or single or combined anti-PD-1 therapy using nivolumab and ipilimumab antibodies. 40,41 Mitotic index appears to have prognostic significance in all UUS, regardless of genotype, with mitotic activity beyond 25/10 HPF (11.16/mm 2 ) having considerably worse survival outcomes. 42 Uterine tumour resembling ovarian sex cord tumour Fusions involving growth regulation by estrogen in breast cancer 1 (GREB1) and estrogen receptor 1 (ESR1) genes have recently been detected in UTROSCT, a mesenchymal tumour of uncertain malignant potential that resembles sex cord stromal tumours of the ovary.…”
Section: Uusmentioning
confidence: 97%
“…In one study, all five died of disease at 1, 4, 7, 9 and 43 months after initial presentation . Patients with SMARCA4‐deficient UUS may benefit from enrolment in ongoing clinical trials using tazemetostat, a selective small molecule EZH2 inhibitor or single or combined anti‐PD‐1 therapy using nivolumab and ipilimumab antibodies . Mitotic index appears to have prognostic significance in all UUS, regardless of genotype, with mitotic activity beyond 25/10 HPF (11.16/mm 2 ) having considerably worse survival outcomes …”
Section: Uusmentioning
confidence: 99%
“…177 In agreement with the known antagonism between the PRC2 and the SWI/SNF complex, it has been recently demonstrated that SCCOHT cells are highly sensitive to EZH2 inhibitors, being EZH2 the catalytic subunit of the PRC2 complex. 178,179 However, the EZH2i tazemetostat 19 only induced disease stabilization or partial response in two SCCOHT patients previously treated with standard chemotherapy (www.epizyme.com).…”
mentioning
confidence: 99%